Fecal and Duodenal Microbiota in Pediatric Celiac Disease - Abdukhakimova, Diyora; Dossybayeva, Kuanysh; Poddighe, Dimitri (Frontiers in Pediatrics, 2021)
Background and objective: The gut microbiota plays a role in regulating the host immunity. Therefore, alterations in gut microbiota (or dysbiosis) have been investigated in several gastrointestinal diseases, including Celiac Disease (CD). The main aim of this study is to summarize the main characteristics of the gut microbiota in pediatric CD. Methods: We performed a systematic review to retrieve the available studies investigating the gut microbiota in pediatric CD patients and controls. In detail, after the screening of >2,200 titles retrieved from the medical literature search, 397 articles were assessed for eligibility based on the abstracts: of those, 114 full-text original articles were considered as eligible according to the aim of this systematic review. Results: The final search output consisted of 18 articles describing the gut microbiota of CD children and including one or more control groups. Eleven pediatric studies provided information on the duodenal microbiota and as many investigated the fecal microbiota; three articles analyzed the microbiota on both fecal and duodenal samples from the same cohort of patients. Conclusion: Due to the heterogeneity of the experimental procedures and design of these studies, it is not possible to evidence any specific celiac signature in the fecal and/or duodenal microbiota of CD children. However, some specific components of the fecal flora and, in detail, Bifidobacterium spp. (e.g. Bifidobacterium longum) may deserve additional research efforts, in order to understand their potential as both probiotic therapy and diagnostic/prognostic biomarker.